(untitled) (Biocenosis, 2015)
Knowledge on biodiversity of primary and high school students was analyzed in twelve rural communities of the country. A total of 524 students participated from third, fifth, seventh and ninth level. The transactional research was based on the species of animals and plants that were mentioned more often by students. Vertebrate and exotic plants were cited the most by the students. The taxonomic knowledge has a less specific level on animals than in plants, and the women knew more about exotic plants than men did. Considering that insects are the most abundant and diverse group in the country and Costa Rican plants constitutes the best-known group so far; this study concludes that teaching and learning on these levels can be improved as part of a National Strategy of Conservation, focusing it towards biodiversity uses and local knowledge of these groups. It is important to consider local student participation and differences in interest and needs according to gender.